Manifestations of Violence in the Novel 'The Infidel' by Ali Badr A Socio-Critical Study - Ahmed, Asst.Prof.Dr. Newzad Ahmed Aswad; Kareem, Asst.Prof.Dr. Idris Kareem Mohammed (Sulaimani Journal for Humanities, 2025)
This research aims to study the novel "The Infidel" by the Iraqi novelist Ali Badr from a social perspective, adopting a socio-critical reading and content analysis approach to examine the novel, in an attempt to identify the manifestations of violence that combine physical, sexual, and psychological violence in the reality of our societies, as indicated by the novel. The phenomenon of violence is one that no society has been spared from, and Iraqi society is one of those that has suffered from acts of violence over long periods of time. Iraqi novels have attempted to expose the forms of violence used, their severity, and to denounce the various crimes resulting from the extensive practice of violence. The novel "The Infidel" is among those that employ the technique of realistic narration in a particular way, paying attention to the artistic aspect as much as to the content of events represented by different forms of violence. It depicts social manifestations steeped in negativity and hatred in Iraqi society, especially after the events of 2003, and more specifically during the ISIS invasion of a large part of Iraq in 2014 and the subsequent years, as addressed in the novel.
Keywords: Physical violence; sexual violence; psychological violence; the socioracial approach; the Iraqi novel